Teaching Reading Strategy Used by A Lecturer in The Classroom - Dewi Syafitri; Moh Hafiz Albaridi; Eco Dzamar Irawan (Linguistic, English Education and Art (LEEA) Journal, 2026)
This study aims to analyze the lecturer’s strategies in teaching reading in the classroom to improve students’ reading comprehension. This research employed qualitative technique and the data were acquired by semi-structured interview to English lecturer. Data from the interview were transcribed, analyzed, classified and categorized into themes to find out the instructional strategies used by the lecturer. The results indicate that the lecturer used a variety of strategies including activating prior knowledge, pre-teaching important vocabulary, skimming, asking guiding questions, inference of meaning from context, discussion, scaffolding, translanguaging, multilingual support and adjusting instruction to students’ different ability levels. These strategies allowed pupils to absorb the text more gradually and more successfully. In short, the lecturer’s teaching strategies are systematic and student-centered, and the use of scaffolding, translanguaging and multilingual support adds to a more inclusive and effective reading class. Keywords: Multilingual Support, Reading Comprehension, Scaffolding, Teaching Reading Strategies, Translanguaging